A simple but powerful tool for the assessment of financial progress in EU co-funded grant programmes – Simple Progress Overview Tool (SPOT) - Mezősi, Balázs (Acta Agraria Debreceniensis, 2014)
Mid-term evaluation of grant programmes always aim to assess the financial progress of the programme. Progress to date assessment is conducted via addressing three issues: by overviewing progress so far, by exploring the reasons behind the current level of progress, and by answering the specific evaluation questions formulated as a result of progress overview. The Simple Progress Overview Tool is a method and a tool facilitating the overview of financial progress, supporting the exploration of reasons behind the current level of progress and enabling the identification of targeted further evaluation questions. The methodology applies the Du Pont approach of division to factors, in which the variable describing a phenomenon is divided into the multiplication of factors (milestone stages of the process) influencing the variable. Also, this division to factors facilitates the identification of reasons behind progress. The factors carry individually meaningful information to the evaluation of progress. This method was used by many EU member states including the Czech Republic, Romania, and Malta for the evaluation of progress in the course of the mid-term evaluation of their National Strategic Reference Frameworks.